Socialization and Training on Income Tax Article 21 Based on the Average Effective Rate (TER) for MSMEs in Watesprojo Village - Dwi Dewianawati; Erry Setiawan; Dian Indrianto; Buyung Cahya Perdana; Harjo Lukito; Ratna Agustina (PT. Gudang Pustaka Cendekia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the national economy; however, tax compliance, particularly related to Income Tax Article 21, remains relatively low. The main challenges faced by MSME actors include limited tax literacy, complexity in tax calculations, and insufficient understanding of recent regulatory changes. To address these issues, the government introduced the Average Effective Rate (TER) scheme as an administrative simplification for calculating Income Tax Article 21. Nevertheless, the implementation of this scheme has not been fully understood by MSMEs at the village level. This study aims to conduct socialization and training on Income Tax Article 21 based on the TER scheme for MSMEs in Watesprojo Village and to evaluate its effectiveness in improving tax understanding and technical capability. The research method involved initial observation, regulatory socialization, practical tax calculation training, and participant evaluation. The results indicate a noticeable improvement in MSME actors’ understanding of the legal basis of Income Tax Article 21, the changes in the calculation scheme, and the practical application of the TER mechanism without disrupting business activities. Overall, the socialization and training activities proved effective in enhancing tax literacy and supporting sustainable tax compliance among MSMEs.